The influence of post-processing methods and frequency bands on rs-fMRI: An example of electroacupuncture at Zusanli (ST36) - YingJie Kang; YiLei Chen; ZhiGang Gong; YanWen Huang; Hui Wang; Jiling Huang; SongHua Zhan; YiJing Li; WenLi Tan (NeuroImage: Reports)
Objective: Electroacupuncture at Zusanli (ST36) exerted an effect on brain function by regulating spontaneous brain activity. This study aims to investigate the influence of different post-processing methods of amplitude of low-frequency fluctuation (ALFF) and different frequency band to measure brain low-frequency oscillations (LFOs) after electroacupuncture at ST36. Methods: Twenty-eight healthy subjects were recruited and received true electroacupuncture (EA) and sham electroacupuncture (SA) at ST36 respectively. The rs-fMRI scans were performed before and immediately after electroacupuncture. Three post-processing methods were used to evaluate the amplitude of LFOs: fractional ALFF (fALFF), percent amplitude of fluctuation (PerAF) and wavelet-transform ALFF (Wavelet-ALFF). Besides the conventional low-frequency band (0.01–0.1Hz), three additional sub-bands were observed, including slow-6 (0–0.01Hz), slow-5 (0.01–0.027Hz) and slow-4 (0.027–0.073Hz). Paired t-test was conducted to investigate the intra-group differences of three post-processing methods before and after each intervention. In the comparison of inter-group difference, the paired t-test was conducted between SA and EA. Results: Electroacupuncture at ST36 increased LFO amplitudes, with more pronounced effects compared to SA. As compared to SA, the fALFF values in the left superior frontal gyrus and orbital middle frontal gyrus increased after EA. Only the EA group showed an increase in Wavelet-ALFF. PerAF was the most sensitive method for detecting LFO amplitude changes and revealed changes in white matter. Additionally, brain LFO changes were frequency-dependent, with more favorable results observed in the conventional low-frequency band and the slow-5 band. Conclusion: Post-processing methods affect the interpretation of brain effects caused by electroacupuncture at ST36. FALFF was suitable for observing brain LFO differences between EA and SA. Wavelet-ALFF was stable but less sensitive. PerAF was a promising method for investigating LFOs in white matter. The brain LFO changes caused by electroacupuncture at ST36 were frequency-dependent.